(untitled) (TAMADDUN NURI JURNALI, 2025)
this article analyzes the psychological features associated with the development of professional skills in medical students. The article highlights effective psychological strategies for creating a significant learning environment that promotes the acquisition of skills and professional growth through a comprehensive analysis of existing psychological theories and educational practices.